High-repetition-rate and high-power picosecond regenerative amplifier based on a single bulk Nd:GdVO4 crystal. (13th June 2019) - Guo, Jie; Wang, Wei; Lin, Hua; Liang, Xiaoyan
Abstract : We report on a high-repetition-rate, high-power continuously pumped Nd:GdVO4 regenerative amplifier. Numerical simulations successfully pinpoint the optimum working point free of bifurcation instability with simultaneous efficient energy extraction. At a repetition rate of 100 kHz, a maximum output power of 23 W was obtained with a pulse duration of 27 ps, corresponding to a pulse energy of 230 [STIX]x03BCJ . The system displayed an outstanding stability with a root mean square power noise as low as 0.3%. The geometry of the optical resonator and the pumping scheme enhanced output power in the TEM_00 mode with a single bulk crystal. Accordingly, nearly diffraction-limited beam quality was produced with M^2≈ 1.2 at full pump power.